Media, society, world : social theory and digital media practice - Couldry, Nick (Polity, 2012)
Media are fundamental to our sense of living in a social world. Since the beginning of modernity, media have transformed the scale on which we act as social beings. And now in the era of digital media, media themselves are being transformed as platforms, content, and producers multiply. - Yet the implications of social theory for understanding media and of media for rethinking social theory have been neglected; never before has it been more important to understand those implications. This book takes on this challenge. - Drawing on Couldry's fifteen years of work on media and social theory, this book explores how questions of power and ritual, capital and social order, and the conduct of political struggle, professional competition, and everyday life, are all transformed by today's complex combinations of traditional and 'new' media. In the concluding chapters Couldry develops a framework for global comparative research into media and for thinking collectively about the ethics and justice of our lives with media.